Predictive factors associated with the persistence of chest pain in post-laparoscopic myotomy and fundoplication in patients with achalasia - Olvera-Prado, Héctor; Peralta-Figueroa, José; Narváez-Chávez, Sofía; Rendón-Macías, Mario E.; Perez-Ortiz, Andric; Furuzawa-Carballeda, Janette; Méndez-Flores, Silvia; Núñez-Pompa, María del Carmen; Trigos-Díaz, Alonso; Areán-Sanz, Rodrigo; López-Verdugo, Fidel; Coss-Adame, Enrique; et al. (Frontiers in Medicine, 2022)
Background Episodic angina-like retrosternal pain is a prevalent symptom for achalasia patients pre- and post-treatment. The cause of postoperative chest pain remains poorly understood. Moreover, there are no reports on their predictive value for chest pain in the long-term post-treatment. The effect of laparoscopic Heller myotomy (LHM) and fundoplication techniques (Dor vs. Toupet) is unclear. Methods We analyzed a cohort of 129 achalasia cases treated with LHM and randomly assigned fundoplication technique. All the patients were diagnosed with achalasia by high-resolution manometry (HRM). Patients were followed up at 1-, 6-, 12-, and 24-month post-treatment. We implemented unadjusted and adjusted logistic regression analyses to evaluate the predictive significance of pre- and post-operative clinical factors. Results Preoperative chest pain with every meal was associated with an increased risk of occasional postoperative chest pain [unadjusted model: odds ratio (OR) = 12, 95% CI: 2.2–63.9, P = 0.006; adjusted model: OR = 26, 95% CI: 2.6–259.1, P = 0.005]. In type II achalasia, hypercontraction was also associated with an increased risk of chest pain (unadjusted model: OR = 2.6 e9 in all the patients). No significant differences were associated with age, type of achalasia, dysphagia, esophageal shape, and integrated relaxation pressure (IRP) with an increased risk of occasional postoperative chest pain. Also, there was no significant difference between fundoplication techniques or surgical approaches (e.g., length of myotomy). Conclusion Preoperative chest pain with every meal was associated with a higher risk of occasionally postoperative chest pain.